US28 Is a Potent Activator of Phospholipase C during HCMV Infection of Clinically Relevant Target Cells - Miller, William E. (Public Library of Science, 2012)
Members of the cytomegalovirus family each encode two or more genes with significant homology to G-protein coupled receptors (GPCRs). In rodent models of pathogenesis, these viral encoded GPCRs play functionally significant roles, as their deletion results in crippled viruses that cannot traffic properly and/or replicate in virally important target cells. Of the four HCMV encoded GPCRs, US28 has garnered the most attention due to the fact that it exhibits both agonist-independent and agonist-dependent signaling activity and has been demonstrated to promote cellular migration and proliferation. Thus, it appears that the CMV GPCRs play important roles in viral replication in vivo as well as promote the development of virus-associated pathology. In the current study we have utilized a series of HCMV/US28 recombinants to investigate the expression profile and signaling activities of US28 in a number of cell types relevant to HCMV infection including smooth muscle cells, endothelial cells and cells derived from glioblastoma multiforme (GBM) tumors. The results indicate that US28 is expressed and exhibits constitutive agonist-independent signaling activity through PLC-β in all cell types tested. Moreover, while CCL5/RANTES and CX3CL1/Fractalkine both promote US28-dependent Ca(++) release in smooth muscle cells, this agonist-dependent effect appears to be cell-specific as we fail to detect US28 driven Ca(++) release in the GBM cells. We have also investigated the effects of US28 on signaling via endogenous GPCRs including those in the LPA receptor family. Our data indicate that US28 can enhance signaling via endogenous LPA receptors. Taken together, our results indicate that US28 induces a variety of signaling events in all cell types tested suggesting that US28 signaling likely plays a significant role during HCMV infection and dissemination in vivo.